Spatio-temporal variations of vegetation cover and its influence on surface air temperature change over the Yellow River Basin, China. Issue 9 (30th August 2022) - Han, Zhenyue; Wu, Qiang; Lai, Ruixun; Soomro, Shan-e-hyder; Hou, Dongru; Hu, Caihong
Abstract: Northwest China has experienced dramatic changes in vegetation cover over the past few decades with the Yellow River Basin (YRB) being the most representative area. As the major climate-sensitive area in China, vegetation cover change is one reason for its impact on surface air temperature (SAT). This study uses the observation minus reanalysis (OMR) method to reveal the spatio-temporal variations of vegetation cover and its impact on SAT change over non-urban areas of the YRB from 1982 to 2015. The Global Inventory Modeling and Mapping Studies dataset, SAT derived from meteorological stations, and European Reanalysis (ERA)-interim reanalysis temperature data were used to analyze the relationship between normalized difference vegetation index (NDVI) and temperature variation caused by vegetation change. The NDVI trend (SlopeNDVI ) of the entire YRB reached 1.11×10 −2 decade −1, which indicated the recovery of vegetation in general. The impact of variation in vegetation conditions on SAT change during 1982–2015 was estimated to be 0.037 °C decade −1, which contributed 7.62% to the temperature change. The mean annual NDVI ( M NDVI ) and SlopeNDVI in the YRB were significantly negatively correlated ( P <0.001) with OMR temperature variation. A negative correlation was exhibited in semi-arid and semi-humid regions, whereas a positive correlation was found in the arid region. The observed changes in vegetation and SAT in the YRB support the theory of the impact of vegetation variation on SAT in China. HIGHLIGHTS: The relationship between vegetation and surface air temperature is different across the climate regions. The spatio-temporal changes of vegetation in non-urban areas of the Yellow River Basin were studied. The contribution rate of the surface air temperature changes caused by vegetation changes during 1982–2015 is 7.62%. The vegetation changes warmed the surface temperature by 0.037 °C decade −1 during 1982–2015. Graphical Abstract